Rancang Bangun Sistem Informasi Manajemen Laundry Pada Klin En Klin Laundry - Arie Rafika Dewi; Nurjamiyah Nurjamiyah (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Klin en Klin is a business that is engaged in clothes washing and ironing services that are starting to develop. Where this laundry business provides kilogram washing services and washing services that are calculated per item including washing and dry services and ironing services such as washing clothes, washing bad covers, washing blankets, washing curtains, washing dolls, washing bags, washing shoes, washing helmets, washing carpets, wash the coat. The management process in this laundry service activity is still manual. In data collection activities, customers' clothes are still very inefficient because data collection is still using paper and handwritten. When the customer comes to hand over the goods, the recording of goods data and making notes is still using paper so that when the data is stored or archived, the data is prone to loss or damage which could result in negligence or natural disaster. In addition, financial statements can also be miscalculated. Transaction systems that are still manual and still not optimal have found problems such as accumulation of records and reports, slow information flow, slow data retrieval process and difficult transaction report recap. To overcome this problem, a laundry management information system is needed that can increase the effectiveness and efficiency of the Klin En Klin Laundry business. The purpose of this research is to produce a web-based software application using the PHP programming language and MySQL database to design a Laundry Management System. The result of this design is to produce a Web-based application that can be a medium of information to help laundry service businesses in managing their management